Sports massage - Ylinen, Jari; Cash, Mel (Stanley Paul, 1988)
Sports therapy has made huge advances in recent years, and is no longer the preserve of the professional athlete. This landmark book is the first to set out in full the techniques and routines involved in sports massage, as well as guidance on the treatment of specific injuries related to various sports.